Effects of dietary supplementation of glutamine and glutamic acid on performance and stress response to high temperature in broiler chickens - Omolayo, Olubodun Joshua (2015)
Glutamine (Gln), a conditionally essential amino acid has been documented to aid animals under stressful condition which include injury, weaning, infection and overcrowding. Reports on the following functions of Gln have been inconsistent hence,the need to ascertain this claims and especially under high temperature. Experiments were conducted to investigate the effects of dietary supplementation of glutamine (Gln) and glutamic acid (Glu) on performance and stress response to high temperature inbro iler chicken. In experiment 1, day-old (day 1) commercial broiler chicks were fed (i) basal diet (control), (ii) basal diet + 0.5% Gln+Glu or (iii) basal diet + 1% Gln+Glu from 1 to 42 days of age under the hot and humid tropical environment. AminoGut (Gln+Glu) is a commercial dietary supplement containing a mixture of L-glutamine (Gln) and L-glutamic acid (Glu). Weight gain and FCR during the starter (day 1-21) and overall (day 1-42) periods improved linearly and quadratically with Gln+Glu supplementation when compared to control. Supplementing birds with Gln+Glu significantly reduced overall mortality rate. At 21 and 42 days of age, intestinal (duodenum and ileum) villi height and crypt depth showed both linear and quadratic positive responses to Gln+Glu supplementation. Intestinal amylase activity increased linearly and quadratically on day 21, and linearly only on day 42. It was concluded that Gln+Glu supplementation was beneficial in improving the growth performance and survivability of broiler chickens under the hot and humid tropical environment. Experiment 2 was conducted to investigate the effects of Gln+Glu supplementation on growth performance and physiological stress response in broilers exposed to cyclic heat stress. Day-old commercial broiler chicks were kept in environmentally controlled rooms and fed basal diet (control) or basal diet + 0.5% Gln+Glu from 1 to 21 days of age. From day 22-42, chicks in one chamber were exposed to 34±1oC for 5 hours daily while the other group of chicks remained under 24oC throughout. Weight gain and FCR were significantly improved during the starter (day 1-21) and overall (day 1-42) periods with Gln+Glu supplementation when compared to control. Supplementing birds with Gln+Glu also significantly reduced mortality rate in birds during the heat challenge period. Provision of Gln+Glu to the heat stressed birds resulted in higher heat shock protein (HSP) 70 expression and serum acute phase protein ovotransferrin concentration (OVT). In conclusion, the beneficial effect of Gln+Glu supplementation on performance and survivability of broilers under heat stress could be attributed to enhanced HSP 70 and OVT synthesis.